2018
DOI: 10.1016/j.cmet.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

AMPK: Sensing Glucose as well as Cellular Energy Status

Abstract: Mammalian AMPK is known to be activated by falling cellular energy status, signaled by rising AMP/ATP and ADP/ATP ratios. We review recent information about how this occurs but also discuss new studies suggesting that AMPK is able to sense glucose availability independently of changes in adenine nucleotides. The glycolytic intermediate fructose-1,6-bisphosphate (FBP) is sensed by aldolase, which binds to the v-ATPase on the lysosomal surface. In the absence of FBP, interactions between aldolase and the v-ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
707
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 848 publications
(726 citation statements)
references
References 139 publications
(205 reference statements)
15
707
0
4
Order By: Relevance
“…Action potentials and synaptic activity are mediated by Na + and Ca 2+ influx through plasma membrane channels, followed by their subsequent extrusion by membrane ion-motive ATPases (Na + and Ca 2+ “pumps”); the attendant consumption of ATP increases the AMP/ATP ratio, resulting in the activation of AMP-activated protein kinase (AMPK). AMPK then phosphorylates and thereby regulates the activities of proteins involved in energy metabolism (glucose transporters and the mTOR pathway), autophagy, and neuronal excitability (Weisová et al, 2009; Ikematsu et al, 2011; Lin and Hardie, 2018; Shah et al, 2017). Calcium is an important signal mediating cellular stress adaptation; Ca 2+ binds to the protein calmodulin, resulting in the activation of kinases that promote the activation of transcription factors including CREB and nuclear factor κB (NF-κB) (Cohen et al, 2015; Saura and Cardinaux, 2017; Snow et al, 2014).…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…Action potentials and synaptic activity are mediated by Na + and Ca 2+ influx through plasma membrane channels, followed by their subsequent extrusion by membrane ion-motive ATPases (Na + and Ca 2+ “pumps”); the attendant consumption of ATP increases the AMP/ATP ratio, resulting in the activation of AMP-activated protein kinase (AMPK). AMPK then phosphorylates and thereby regulates the activities of proteins involved in energy metabolism (glucose transporters and the mTOR pathway), autophagy, and neuronal excitability (Weisová et al, 2009; Ikematsu et al, 2011; Lin and Hardie, 2018; Shah et al, 2017). Calcium is an important signal mediating cellular stress adaptation; Ca 2+ binds to the protein calmodulin, resulting in the activation of kinases that promote the activation of transcription factors including CREB and nuclear factor κB (NF-κB) (Cohen et al, 2015; Saura and Cardinaux, 2017; Snow et al, 2014).…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…Although AMPK is classically activated in response to rising AMP/ATP ratios, recent studies have demonstrated that V‐ATPase plays a role in AMP‐independent AMPK activation. Thus, binding of aldolase to V‐ATPase in the absence of the glycolytic intermediate fructose‐1,6‐bisphosphate results in AMPK activation 10, 11…”
Section: V‐atpase Structure and Function In Normal Physiologymentioning
confidence: 99%
“…In addition, there is a growing base of reviews focusing on different aspects of AMPK, such as the functions of AMPK in various tissues, or (patho-)physiological contexts (e.g., [1,2,3,4]). For AMPK novices, Hardie provides an excellent overview (e.g., [5,6,7,8]). In a nutshell, AMPK is an energy-sensing kinase that functions to maintain cellular and whole body energy balance [9].…”
Section: About Ampk and Tak1mentioning
confidence: 99%